Вклад академіка М.Ф. Кащенка у розвиток теорії і практики інтродукції рослин в Україні - Klimenko, S.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2003)
Activity of academician M.Ph. Kashchenko in area of introduction and acclimatization of plants during the different periods of his life is discribed. The period of becoming of acclimatization and selection fruit, medicinal and ornamental plants in the north of Ukraine is considered.